STUDENTS' INTEREST IN EXTRACURRICULAR FUTSAL SPORTS ACTIVITIES AT STATE MIDDLE SCHOOL 45 MEDAN - Forsan Prihastowo; Saputra, Iwan; Nasution, Usman; Harahap, Agustin Sastrawan (Universitas Negeri Medan, 2025)
This study aims to determine the level of student interest in futsal extracurricular activities and the factors that influence it at State Junior High School 45 Medan. The method used is a qualitative descriptive method with a survey approach using an instrument in the form of a closed questionnaire consisting of 42 statements. The subjects in this study were 30 students who participated in futsal extracurricular activities. The results of the study showed that the majority of students had a high interest in futsal extracurricular activities. Overall, the results of the study were that 23% of students were in the very high interest category, 60% of students were in the high interest category, 7% of students were in the medium interest category, 7% of students were in the low interest category, and 3% of students were in the very low interest category. Factors that influence student interest are classified into two, namely intrinsic factors (attention, feelings of pleasure, and activity) and extrinsic factors (the role of teachers/coaches, facilities, family support, and the environment). Both factors significantly contribute to the level of student interest in participating in futsal activities at school. This study demonstrates that the success of futsal extracurricular activities is significantly influenced by the efforts of coaches, the availability of adequate facilities, and a supportive environment. These findings are expected to inform evaluation and improvement for schools in managing and developing extracurricular programs to make them more engaging and beneficial for students.